Digital Literacy and Ethics in the Concept of Global Citizenship: A Study on Social Media Use - Susi Anita Patmawati; Dewilna Helmi; Dwi Partini (Universitas Negeri Gorontalo, 2026)
The development of digital technology and the widespread use of social media have changed the way people communicate and participate in various issues at the global level. The concept of global citizenship now not only includes identity and responsibility within geographical boundaries but also involves digital ethics and literacy in communicating in cyberspace. This study aims to explore the role of digital literacy and ethics in shaping global citizenship awareness among social media users, and this can help reduce social conflict and increase social responsibility in global interactions. This study uses a qualitative method with descriptive data exposure with case studies of social media users in Indonesia. Data were collected through in-depth interviews and content analysis from various social media platforms (Instagram, Facebook, and TikTok). The results of the study show that the majority of social media users do not reflect adequate digital literacy and ethics in the concept of global citizenship. Of the 1,000 data analyzed, 60% of them contain negative comments that are not by the principles of digital ethics. These findings underline the importance of digital literacy and ethics knowledge in creating a more positive and responsible interaction space in the global era. This study contributes to the development of a more inclusive and ethical concept of global citizenship in the real world. The limitations of this researcher lie in direct interaction with respondents.